DEVELOPMENT OF THE METHOD OF OPTIMUM ADJUSTMENT AREAS FOR THE ORGANIZATION OF HIGH-SPEED RAILWAY TRAINS - Kurhan, M. B. (Science and Transport Progress, 2006)
The proposed optimization method is based on usage of a non-additive function of cutting the train running time upon sections (facilities), subject to reconstruction. The effect in the optimization procedure is being reached thanks to introduction of new semi-additive (from bottom and from top) functions, which reduces the optimization time in comparison with linear search of the options.